The Effect of Sharia Supervisory Board Characteristics and Sharia Compliance on Islamic Social Reporting Disclosure (Financial Performance as a Moderating Variable) - Ulvatiani , Huti; Fakhruddin, Iwan; Kusbandiyah, Ani; Amir (Jurnal Ekonomi dan Bisnis Digital, 2024)
The purpose of this study was to examine the effect of  characteristics of the sharia supervisory board and sharia compliance on Islamic Social Reporting reporting with financial performance as a moderating variable on sharia compliance. The type of quantitative research with the sample used in this research is Sharia Commercial Banks in 2017-2022 with a total 80 samples. This study uses three stages of data analysis to determine the most appropriate multiple linear regression model. The tests carried out consisted of the Hausman test, the Breusch and Pagan multiplier test, and the Chow test. Based on these three models, it shows that this study will use the ordinary least square model. Then the diagnostic test, namely normality test, multicollinearity, heteroscedasticity.